Monitoring of analgesia level during general anesthesia in children. Issue 3 (June 2022) - Sabourdin, Nada; Constant, Isabelle
Abstract : Purpose of review: Monitoring of intraoperative nociception has made substantial progress in adult anesthesia during the last 10 years. Several monitors have been validated and their use has been associated with intraoperative or postoperative benefits in the adult population. In pediatric anesthesia, less data are available. However, several recent publications have assessed the performance of nociception monitors in children, and investigated their potential benefits in this context. This review will describe the main validated intraoperative nociception monitors, summarize adult findings and describe the available pediatric data. Recent findings: Six intraoperative nociception indices were included in this review. Among them, four have shown promising results in children: Surgical Pleth Index (GE-Healthcare, Helsinki, Finland), Analgesia-Nociception Index (Mdoloris Medical Systems, Loos, France), Newborn-Infant Parasympathetic Evaluation (Mdoloris Medical Systems), and Pupillometry (IDMED, Marseille, France). The relevance of Skin Conductance (MedStorm innovations, AS, Oslo, Norway) under general anesthesia could not be established. Finally, the Nociception Level (Medasense, Ramat Gan, Israel) still requires to be investigated in children. Summary: To date, four monitors may provide a relevant assessment of intraoperative nociception in children. However, the potential clinical benefits associated with their use to guide analgesia remain to be demonstrated.